2015
DOI: 10.1021/acs.orglett.5b00637
|View full text |Cite
|
Sign up to set email alerts
|

Breaking and Making of Olefins Simultaneously Using Ozonolysis: Application to the Synthesis of Useful Building Blocks and Macrocyclic Core of Solomonamides

Abstract: A simple and practical one-pot, two-directional approach to access olefinic esters through simultaneous breaking and making of olefins using ozonolysis of alkenyl aryl selenides is disclosed. The scope of the method with a variety of examples is demonstrated, and the end products obtained here are useful building blocks. As a direct application of the present method, the macrocyclic core of potent anti-inflammatory natural cyclic peptides, solomonamides, is synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Accordingly, to a solution of lactam 8 and acid 21 in CH 2 Cl 2 , DMAP, 2-methyl-6-nitrobenzoic anhydride (MNBA) and triethyl amine were added, to afford hoshinolactam (1) in 76 % yield (Scheme 5). Here, the synthesized compound is diastereomeric mixture (racemic cyclopropane) even though the spectral data ( 1 H and 13 C NMR) are in complete agreement with the reported data. [9] Comparison of the 1 H and 13 C NMR spectra of both the compounds are provided in the supporting information.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Accordingly, to a solution of lactam 8 and acid 21 in CH 2 Cl 2 , DMAP, 2-methyl-6-nitrobenzoic anhydride (MNBA) and triethyl amine were added, to afford hoshinolactam (1) in 76 % yield (Scheme 5). Here, the synthesized compound is diastereomeric mixture (racemic cyclopropane) even though the spectral data ( 1 H and 13 C NMR) are in complete agreement with the reported data. [9] Comparison of the 1 H and 13 C NMR spectra of both the compounds are provided in the supporting information.…”
Section: Resultssupporting
confidence: 86%
“…Here, the synthesized compound is diastereomeric mixture (racemic cyclopropane) even though the spectral data ( 1 H and 13 C NMR) are in complete agreement with the reported data. [9] Comparison of the 1 H and 13 C NMR spectra of both the compounds are provided in the supporting information.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, in the particular case of the solomonamides, the scarce availability of T. swinhoei clearly conditioned the further characterization of the compounds’ bioactivities. In the last years, different studies toward the synthesis of solomonamides have been reported, mainly by Reddy et al [15,17,37,38,39,40,41]. In fact, very recently, the total syntheses of solomonamides A and B have been reported [13], which led to their stereochemical revision with respect to that initially proposed, and confirmed the anti-inflammatory activities reported for the natural products.…”
Section: Discussionmentioning
confidence: 77%
“…One possible way to make sulfoxide is by the use of sodium metaperiodate, however, it generates a considerable amount of solid waste. But here we have utilized ozonolysis reaction to convert sulfur to sulfoxide in CH 2 Cl 2 at –78 °C which also makes it a greener approach . Crude sulfoxide thus obtained was subjected for pyrolytic elimination in the presence of calcium carbonate in ODCB ( o ‐dichloro benzene) as solvent under reflux condition to result in compound 5a with an overall yield of 40 % over two steps .…”
Section: Resultsmentioning
confidence: 99%